Self‐Complementary Dimers of Oxalamide‐Functionalized Resorcinarene Tetrabenzoxazines. Issue 2 (18th December 2017) - Džolić, Zoran; Beyeh, Ngong Kodiah; Cetina, Mario; Turunen, Lotta; Rissanen, Kari
Abstract: Self‐complementarity is a useful concept in supramolecular chemistry, molecular biology and polymeric systems. Two resorcinarene tetrabenzoxazines decorated with four oxalamide groups were synthesized and characterized. The oxalamide groups possessed self‐complementary hydrogen bonding sites between the carbonyls and amide groups. The self‐complementary nature of the oxalamide groups resulted in self‐included dimeric assemblies. The hydrogen bonding interactions within the tetrabenzoxazines gave rise to the formation of dimers, which were confirmed by single‐crystal X‐ray diffractions analysis and supported by NMR spectroscopy and mass spectrometry. The self‐included dimers were connected by numerous and strong intermolecular N−H⋅⋅⋅O and C−H⋅⋅⋅O hydrogen bonds supplemented with C−H⋅⋅⋅π interactions, forming one‐dimensional polymers, which were then further linked into three‐dimensional networks. Abstract : Decorated bowls : Two resorcinarene tetrabenzoxazines decorated with four oxalamide groups form self‐complementary dimers through concerted hydrogen bonds between the carbonyl and amide groups of the oxalamide moieties. The self‐complementary dimers are confirmed by single crystal XRD analysis, NMR spectroscopy and mass spectrometry.